A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region - Poppe, Jean Lucas; Valente, Vera Lúcia Da Silva; Dos Santos, João Pedro Junges; Gottschalk, Marco Silva (Zootaxa, 2016)
The genus Rhinoleucophenga Hendel comprises 29 nominal species with New World distribution. In the present study five species are redescribed: R. angustifrons Malogolowkin; R. lopesi Malogolowkin; R. matogrossensis Malogolowkin; R. nigrescens Malogolowkin and Rhinoleucophenga personata Malogolowkin. R. capixabensis Culik & Ventura is proposed as a new junior synonymy of R. lopesi. Other species, R. jacareacanga sp. nov., is described from the specimens deposited at CEIOC/Fiocruz. The description of new species and review of some former descriptions of Rhinoleucophenga is indispensable since the distribution records of some species are doubtful.